PIROLISIS SERBUK KAYU MERANTI (SHOREA) DENGAN INSTRUMEN PYROLYSIS-GAS CHROMATOGRAPHY-MASS SPECTROSCOPY - Miranda Miranda; RR Dirgarini Julia Nurlianti Subagyono; Rahmat Gunawan (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
A study on the pyrolysis of meranti (Shorea) sawdust using a pyrolysis-gas chromatography-mass spectrometry (Py-GC/MS) instrument was carried out. This research was conducted to determine the chemical and physical characteristics of meranti (Shorea) sawdust and to determine the chemical composition of the meranti (Shorea) pyrolysis product. Pyrolysis was carried out with three different temperature variations, namely 350°C, 450°C and 550°C. Meranti wood powder (Shorea) has a moisture content of 12±0.001%, an ash content of 0.07±0.017%, a -cellulose content of 66%, a lignin content of 35±0.047% and a hemicellulose content of 2%. Based on the percentage of product area in the pyrolysis pyrolysis, meranti (Shorea) sawdust contains lignin derivative products (29-50%) and cellulose/hemicellulose derivative products (7-17%). The pyrolysis product with the highest percent area was carbamic acid monoammonium salt. (E)-2,6-Dimethoxy-4-(prop-1-en-1-yl)phenol. Phenol, 4-ethenyl-2,6-dimethoxy-. Acetic acid. Ammonium acetate. Butanenitrile, 3-oxo- and Beta.-D-Glucopyranose, 1,6-anhydro. Keywords: Pyrolysis, Py-GC/MS, Meranti wood powder (Shorea)